Polyhydroxyalkanoates (PHA) production from synthetic waste using Pseudomonas pseudoflava: PHA synthase enzyme activity analysis from P. pseudoflava and P. palleronii. (June 2017) - Venkateswar Reddy, M.; Mawatari, Yasuteru; Onodera, Rui; Nakamura, Yuki; Yajima, Yuka; Chang, Young-Cheol
Highlights: PHA production from synthetic waste using P. pseudoflava was evaluated. High carbon content present in the waste was successfully degraded by bacteria. Produced PHA was characterized by NMR, GPC, DSC and TGA. PHA synthase enzyme was characterized from P. pseudoflava and P. palleronii . PHA production from waste reduces treatment cost & production cost. Abstract: Synthetic wastewater (SW) at various carbon concentrations (5–60 g/l) were evaluated for polyhydroxyalkanoates (PHA) production using the bacteria Pseudomonas pseudoflava . Bacteria showed highest PHA production with 20 g/l (57 ± 5%), and highest carbon removal at 5 g/l (74 ± 6%) concentrations respectively. Structure, molecular weight, and thermal properties of the produced PHA were evaluated using various analytical techniques. Bacteria produced homo-polymer [poly-3-hydroxybutyrate (P3HB)] when only acetate was used as carbon source; and it produced co-polymer [poly-(3-hydroxybutyrate-co-3-hydroxyvalerate) P(3HB-co-3HV)] by addition of co-substrate propionate. PHA synthase, the enzyme which produce PHA was extracted from two bacterial strains i.e., P. pseudoflava and P. palleronii and its molecular weight was analysed using SDS-PAGE. Protein concentration, and PHA synthase enzyme activity of P. pseudoflava and P. palleronii was carried out using spectrophotometer. Results denoted that P. pseudoflava can be used for degradation of organic carbon persistent in wastewaters and their subsequent conversion into PHA.